Analysis of Making LKPD Based on the 7E Learning Cycle Model to Empower Critical and Creative Thinking (CCT) Skills - Winda Annisha Bertiliya; Dwi Yulianti; Ryzal Perdana (Budapest International Research and Critics University, 2023)
Student Worksheet (LKPD) is a supporting tool as a tool to facilitate students in carrying out learning and learning activities well. So that it is expected to form interactions in the form of critical and creative thinking. This study aims to form a synchronized LKPD using the 7E learning model which is expected to be able to empower students' critical and creative thinking. The 7E learning model consists of seven well-organized phases, namely eliciting, engagement, exploring, explaining, elaborating, evaluating, and expanding. The method used in this study is qualitative research using a test in the form of 10 description questions and questionnaires to be conducted on 28 fourth grade students A SD N 1 Labuhan Ratu Bandar Lampung, as well as a literature study. study by reviewing several journals relevant to the topic. study. The results of data analysis obtained in the form of students who are less interested in participating in the ongoing learning process because the media delivered by educators is less attractive and seems monotonous. The average of the researchers' findings from their investigation of the test recapitulation is 23.11%, with very low standards. In addition to tests, researchers also distributed questionnaires to find out the extent of students' critical thinking and creative thinking skills, so that there was a questionnaire recapitulation result that researchers averaged 57.43% with fewer criteria.